2017
DOI: 10.1002/jsfa.8301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a polysaccharide‐rich hydrolysate from Saccharomyces cerevisiae (LipiGo®) in body weight loss: randomised, double‐blind, placebo‐controlled clinical trial in overweight and obese adults

Abstract: Journal of the Science of Food and Agriculture publishes peer-reviewed original research, reviews, and perspectives in these areas, with particular emphasis on interdisciplinary studies at the agriculture/food interface. The journal focuses on hypothesis-driven research studies suitable for an international audience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…The mean trial duration was 17 weeks (range 4–52 weeks) and mean study size was 79 participants (range 12–250). The studies were conducted in New Zealand [37], the United Kingdom [23], the United States [38,39], Canada [31,40], Italy [29,30], Japan [26], Germany [6,30], Mexico [32], Singapore [41] and Spain [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean trial duration was 17 weeks (range 4–52 weeks) and mean study size was 79 participants (range 12–250). The studies were conducted in New Zealand [37], the United Kingdom [23], the United States [38,39], Canada [31,40], Italy [29,30], Japan [26], Germany [6,30], Mexico [32], Singapore [41] and Spain [33].…”
Section: Resultsmentioning
confidence: 99%
“…Various clinical trials have been performed in the past 25 years investigating the effect of chitosan on body weight, body mass index (BMI), lipid parameters, blood pressure, glucose levels and other health characteristics [6,29,30,31,32,33]. The last meta-analysis quantifying these studies (the Cochrane systematic review of Jull 2008) concluded that these effects were probably not of clinical significance [34].…”
Section: Introductionmentioning
confidence: 99%
“…A randomised, double-blind, placebo-controlled clinical trial testing BG from Saccharomyces cerevisiae was performed in overweight and obese subjects (3 g/day) for 12 weeks. Results indicated that daily supplementation was useful for improving body weight and waist circumference, without adverse effects [77]. Meta-analysis evaluating the effect of oat BG intake on glycaemic control of diabetic patients (using only randomized controlled trials) indicated that BG ingestion significantly lowered concentrations in fasting plasma glucose and glycosylated hemoglobin (HbA1c) [78].…”
Section: Discussionmentioning
confidence: 99%
“…In that study, body weight and waist circumference were also reduced when compared to Placebo after 3 months of treatment. Importantly, participants were not enrolled in a body weight loss program [ 19 ]. Then, the present study results on body weight and waist circumference reduction support the efficacy of Lipigo ® even when combined with a controlled diet.…”
Section: Discussionmentioning
confidence: 99%
“…Lipigo ® is a polysaccharide-rich fraction containing β-glucan, chitin, and chitosan, obtained by a specific hydrolysis procedure of residual S. cerevisiae from brewery. A previous randomized, double-blind, placebo-controlled small trial demonstrated a statistically significant benefit of Lipigo ® on body weight management in overweight and obese population over 12 weeks [ 19 , 20 ]. In the present study, we sought to replicate the previous findings in a more robust randomized clinical trial, comprising a significantly bigger sample size, a better dietary control, and a longer treatment and follow-up periods.…”
Section: Introductionmentioning
confidence: 99%